Detecting spatiotemporal variability in the physicochemical properties of water in the Lower Mearim using remote sensing data - Silva Filho, George Colares; Santos, Juliana Martins dos; Villis, Paulo Cesar Mendes; Gonçalves, Ingrid Santos; Correia, Isael Coelho; Costa, Paulo Henrique de Oliveira; Santos, Diego Rosa dos; Ferreira, Juliana Karolliny da Silva; Silva, Fabrício Brito (Ciência e Natura, 2020)
Natural or anthropogenic chemical compounds of different origins often accumulate in estuarine regions. These compounds may alter the water quality. Therefore, It is important to constantly monitor the quality of estuarine regions. A combination of remote sensing and traditional sampling can lead to a better monitoring program for water quality parameters. The objective of this work is to assess the spatiotemporal variability of the physicochemical properties of water in the lower region of the Mearim River and estimate water quality parameters via remote sensing. Samples were collected at 16 points, from Baixo Arari to the mouth of the watershed, using a multiparameter meter and Landsat 8 satellite images. The physicochemical parameters of the water had high salinity levels, between 2.30 and 20.10 parts per trillion; a high total dissolved solids content, between 2.77 and 19.70 g/L; and minimum dissolved oxygen values. Estimating the physicochemical properties of the water via remote sensing proved feasible, particularly in the dry season when there is less cloud cover.